Taxonomy of Ogu nominal shift to Yoruba - Senayon, Ester (Pedagogika Społeczna Nova, 2023)
Ogu has been experiencing nominal language shift among its speakers, through the agency of Yorubaization, from the turn of the 19th century. Yorubaization is the conversion of anything to more Yoruba norms, which may come in diverse forms such as names, language and other styles or character. Yorubaization of Ogu personal names to spellings and pronunciations that make them look and sound Yoruba, the dominant language in Southwestern Nigeria, has become a common trend among Ogu people, especially the adults. Studies on Yorubaization and even Anglicization, have focused mainly on reasons, effects, patterns and consequences. Such studies do not only suggest that distortion of names is a recent trend, but have also conceded its practice to young people in the main. This study, however reveals that Yorubaization has been a practice of Ogu people, a minority linguistic group in Southwestern Nigeria, since the turn of the 19th century and the trend is not only common among youths, but transference from adults, who have been involved in it, to their children. The study examines the precipitating circumstances that led to Ogu people denying their identity at a time when such practice was rare in Nigeria, with a view to assessing its impact on the affirmation of Ogu individual and group identity in a multilingual, multi ethnic setting. The research methodology, which was qualitative, employed the instruments of participant observation and key informant interviews (KII). A total of 20 family names that have been Yorubaized, across Lagos and Ogun States, were purposively collected. Data gathered were subjected to descriptive, and content analyses. Findings reveal that Yorubaization is a direct consequence of language shift fuelled by inferiority complex, shame and an attempt to deny self. The practice has further engendered language shift, which, in turn, has aggravated the minority status of Ogu people.